The Effect of Training in Various Kinds of Active Bottom Drill Drills on Increasing Pasing Accuracy Down Onupper Class Boys Students of Primary School Perumnas Condongcatu - Dermawan, Budi (Journal of Elementary School Education, 2024)
This study aims to determine the effect of various types of active lower passdrill drills on increasing the accuracy of the lower pass in the volleyballgame of upper class male students at SD Perumnas Condongcatur. Thisresearch uses an experimental method, the research design is "ControlGroups Pretest-Posttest Design". PopulationIn this research, there were 24male students from the upper class at SD Perumnas Condongcatur. Thesample taken from the total sampling results was 24 students. Theinstrument used to test the accuracy of the lower fitting is the modifiedBraddy Volley Ball Test.Data analysis uses the t test. The results of theanalysis show that: (1) There is a significant effect of practicing varioustypes of active bottom pass drill drills on increasing pass accuracy involleyball games for upper class male students at SD PerumnasCondongcatur., witht count5,409> t table 2.20, and a significance value of 0.000 < 0.05, a percentage increase of 22.22%. (2) The experimental groupwith various kinds of active lower fitting drill drills was better at increasingthe accuracy of lower fitting male students in the upper classes of SDPerumnas Condongcatur than the control group, with t count2,902> t table = 2.07 and sig. 0.008 < 0.05 and the average difference is 3.6667.